Stoisisme Kristen: Dari Amor Fati kepada Amor Deus - Jadi Sampurna Lima (Societas Dei: Jurnal Agama dan Masyarakat, 2023)
This article explains the relationship between Greco-Roman Stoicism and Stoicism in the Christian tradition by examining the primary and secondary sources of Cicero, Epictetus, Augustine, and Calvin. The theological-philosophical analysis will examine how theology, worldview, and the Gospel in â€œChristian Stoicismâ€ as found in Calvinâ€™s ethics have made it distinctive from Greco-Roman Stoicism. Superficially, there are similarities between the teachings of Calvinâ€™s ethics and the ethics of Greco-Roman Stoicism. However, the two have sharp differences at their roots, namely at the theological, worldview, and eschatological levels. The ethical advice of these two groups may be similar in several respects, but they are rooted in radically different reasons.